The followers in the feminist directing experience in the contemporary theater: ((Awateef Naim example)) - Mohamed, Amaar abed Selman (Al-Adab Journal, 2020)
The research deals with the most important types of directing experiments for the feminist theater, and the mechanism of women as a director of her own creative art industry is different from the director’s achievement that affected her. The study came to analyze this achievement in four chapters. The second topic included the first researcher presented what the feminist theater and its history and experiences and the second researcher touched through this study to the experiences of women as a theater director and what are its achievements and its effects on creativity in the global arena In the third chapter, the researcher identified the research community and chose the sample director (Awatif Naim), which formed part of the feminist theater experiments and the method of sample analysis of the fourth chapter researcher extracted the results of his research and achieve the objective of the study as well as the conclusions and the list of sources, references and abstract in English.